The Narrative Turn: Interdisciplinary Methods and Perspectives. Issue 3 (1st September 2020) - Sarah, Raine
Abstract: The narrative turn in the social sciences has affected a variety of disciplines and inspired interest in narrative analysis from a range of methodological perspectives. This article provides an overview of the narrative turn, summarizing historic narrative trends in the social sciences which led to the current interest in narrative analysis across a variety of disciplines. I discuss general concerns of narrative definition, data collection and the researcher's voice in presentation before outlining various frameworks for categorizing approaches to narrative analysis. Examples of a variety of narrative analysis perspectives and methods are provided to support this discussion. While the subjective emphasis of narrative analysis has particular relevance for anthropologists, the strength of the field lies in its ability to bring together perspectives and insights from a wide range of fields.